Keanekaragaman dan aktivitas serangga pengunjung pada bunga wortel - Tarigan, Rasiska; Barus, Susilawati; Hutabarat, Rina C.; Sembiring, Perdinanta; Parhusip, Dorkas; Udiarto, Bagus Kukuh; Aryani, Dewi Sartika (Jurnal Entomologi Indonesia, 2022)
Pollinating insects act as agents for transferring pollen to the pistil that leads to the increase of quality seed production. Since carrot is propagation through seed, insect pollination are important in the reproduction of the crop. The purpose of this study was to observe the diversity and activity of pollinating insects on carrot flowers in the Experimental Garden of the Agricultural Technology Research and Assessment Installation (IP2TP) Berastagi. Scan sampling method was applied to record the pollinator diversity, while the foraging behaviour of the insects was observed using focal sampling. The number of insects were recorded, collected and preserved in ethanol 70%. Insect identification guideline book was used to identify the insects by comparing their morphology and physiology.  The results showed that there were 8 insect species visiting the carrot flowers: Apis mellifera Linnaeus, Polyrachis sp., Coccinella sp., Rhagonycha sp., Muscidae sp., Chrysomya sp., Nephrotoma sp. and Tabanus sp. A. mellifera was found to have the highest intensity visiting the carrot flowers (21.6 ± 10.06)% while the lowest was demonstrated by Polyrachis sp. (12.6 ± 4.12)%. Also, A. mellifera was recorded to be the most active insect (11.84 ± 1.46 seconds/flower) with the number of flowers visited was 5,06 ± 1,46 flowers/minute. Polyrachis sp. has been revealed to have the longest stay on the flowers visited (49.24 ± 3.89 seconds/flower) with the number of flowers visited 1.21 ± 3.90 flowers/minute. The diversity of pollinating insect was found to be in intermediate level (H’ = 1.89).